2017
DOI: 10.1038/s41598-017-07795-4
|View full text |Cite|
|
Sign up to set email alerts
|

Spiral Form of the Human Cochlea Results from Spatial Constraints

Abstract: The human inner ear has an intricate spiral shape often compared to shells of mollusks, particularly to the nautilus shell. It has inspired many functional hearing theories. The reasons for this complex geometry remain unresolved. We digitized 138 human cochleae at microscopic resolution and observed an astonishing interindividual variability in the shape. A 3D analytical cochlear model was developed that fits the analyzed data with high precision. The cochlear geometry neither matched a proposed function, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(91 citation statements)
references
References 42 publications
7
83
0
1
Order By: Relevance
“…They argue that logarithmic models are good enough to predict the metric length of the cochlear duct, but fail to predict the details of the spiral shape. Therefore, they developed a polynomial model that requires assessment of the basic individual parameters of cochlear base width, length and their intersection by the modiolus 25 . Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…They argue that logarithmic models are good enough to predict the metric length of the cochlear duct, but fail to predict the details of the spiral shape. Therefore, they developed a polynomial model that requires assessment of the basic individual parameters of cochlear base width, length and their intersection by the modiolus 25 . Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…The cochlea models were derived from parameters of the scala spine and cross-sectional areas previously used in studies, representing the whole cochlea size, producing a 50 µL model which was then scaled to create a 40 µL model 30,31 . These models reflected human total cochlear volume but did not implement a structure for the basilar membrane as there were no barriers between the scalae, allowing the electrode array to be positioned anywhere in the model.…”
Section: Electrocochleography (Ecochg) Recording and Analysis Ecochgmentioning
confidence: 99%
“…However, other taxa that spend more time in deeper waters, for example Pseudorca crassidens (false killer whale) and Tursiops truncatus, also occupy this region of morphospace, indicating that additional factors are also in play, although they may also frequent shallower waters or have coastal ecotypes (Jefferson, Webber & Pitman, 2015). Previous studies have also suggested that constraints on cochlear morphology are strong, due to several factors including frequency propagation (Manoussaki et al, 2008), spatial constraints (Pietsch et al, 2017), and its vital importance for survival in odontocetes (Ketten,1992a). As such the capacity for elaboration or innovation in cochlear shape may be limited, which could force all odontocete cochleae to fall within the same limited morphospace.…”
Section: Discussionmentioning
confidence: 99%